2015
DOI: 10.1109/lwc.2014.2374177
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Characterization of Adjacent Satellite Interference for Earth Stations on Mobile Platforms Operating at Ku and Ka Bands

Abstract: This letter analytically derives the statistical distribution of the Carrier-to-Noise-plus-Interference Ratio (CNIR) due to adjacent satellite interference for earth stations on mobile platforms (ESOMPs) operating in Ku-and Ka-frequency bands. At these bands, the adjacent satellite interference problem which is especially pronounced for mobile terminals is further aggravated by propagation effects, predominantly rain attenuation. The statistical characterization of the resulting CNIR is of paramount importance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…From the time-series slow varying signal component 10 log 10 ๐ฟ ๐‘… , we have obtained several features that includes-(1) time averaged mean of the signal (๐‘‹ ๐‘š ) (2) standard deviation (๐‘‹ ๐œŽ ), (3) skewness (๐‘‹ ๐‘  ), ( 4) kurtosis (๐‘‹ ๐‘˜ ), ( 5) CCDF with the signal value exceeding 1, 2, 3, 4 dB and its mean value denoted in the respective order as ๐‘‹ ๐‘ = [๐‘‹ 1 ๐‘ , ๐‘‹ 2 ๐‘ , ๐‘‹ 3 ๐‘ , ๐‘‹ 4 ๐‘ , ๐‘‹ ๐‘š ๐‘ ]. These extracted features from the time-series slow varying signal 10 log 10 ๐ฟ ๐‘… is then fed into the SVM algorithm that predicts the fast varying signal parameters-bandwidth, mean 6 which shows that there is a good correlation between the variables in consideration.…”
Section: Svm Model and Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the time-series slow varying signal component 10 log 10 ๐ฟ ๐‘… , we have obtained several features that includes-(1) time averaged mean of the signal (๐‘‹ ๐‘š ) (2) standard deviation (๐‘‹ ๐œŽ ), (3) skewness (๐‘‹ ๐‘  ), ( 4) kurtosis (๐‘‹ ๐‘˜ ), ( 5) CCDF with the signal value exceeding 1, 2, 3, 4 dB and its mean value denoted in the respective order as ๐‘‹ ๐‘ = [๐‘‹ 1 ๐‘ , ๐‘‹ 2 ๐‘ , ๐‘‹ 3 ๐‘ , ๐‘‹ 4 ๐‘ , ๐‘‹ ๐‘š ๐‘ ]. These extracted features from the time-series slow varying signal 10 log 10 ๐ฟ ๐‘… is then fed into the SVM algorithm that predicts the fast varying signal parameters-bandwidth, mean 6 which shows that there is a good correlation between the variables in consideration.…”
Section: Svm Model and Predictionmentioning
confidence: 99%
“…T HE congestion at lower frequency bands requires that the satellite links are designed at higher frequency bands to meet the global requirements of growing consumer services at all places with all weather availability [1], [2]. However, the higher frequency bands above 10 GHz suffer more from the atmospheric effects [3].…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 Wireless Communications and Mobile Computing (a) Indicating equation ( 1), it can be seen that the CNIR depends on the CNR and CIR ratios. In addition, CIR in turn depends also on the INR ratio [8]: C/I (dB) = C/N (dB) โˆ’I/N (dB) this means that the CNIR criteria implicitly include all performance metrics (b) The CNIR has been used in many studies, such as [25] which concluded that at the frequency bands (Ku, K, and Ku), the interference problem of adjacent satellites, essentially clear for spotbeam/cell edge terminals, becomes more exacerbated by propagation effects, mainly attenuation by rain. In addition, the CNIR is of supreme significance in the design of new satellite broadband systems based on digital video broadcasting (DVB) (c) In cellular systems for example [26], the probability distribution of the CNIR has a significant task in performance evaluation of the system, managing of the radio resource, and planning of the radio network.…”
Section: System Protection Criteriamentioning
confidence: 99%
“…The framework of space-based AIS is shown in Figure 1. In Figure 1, due to the openness of satellite channels, satellite communication is easily disturbed by external signals, therefore, it is great significance to study the security of satellite communication in space-based AIS (Kourogiorgas et al, 2015) (Chen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%